Recording Risk Factors of Physical Abuse in Children Younger Than 36 Months With Bone Fractures: A 12-Years Retrospective Study in an Italian General Hospital Emergency Room - Castagnino, Miriam; Paglino, Alessandra; Berardi, Carla; Riccioni, Sara; Esposito, Susanna (Frontiers in Pediatrics, 2020)
Skeletal fractures (SFs) are very common in pediatrics. In some cases, they are secondary to child abuse. Differentiation of accidental from nonaccidental fractures (NAFs) is essential as in abused children risk of further injuries leading to severe clinical problems and death is significant. Main objectives of this study were to evaluate the characteristics of SFs of children ≤3 years of age presenting to the Emergency Room (ER) of a Children’s Teaching Hospital over a 12-year period and the attention paid by ER physicians to the identification of the indicators that increase suspicion of NAF and that suggest referring of the patient to the child protection agencies. This is a descriptive, retrospective study of the medical records of all the pediatric patients ≤ 36 months of age admitted to the ER of the Azienda Ospedaliera Santa Maria della Misericordia, University of Perugia, Perugia, Italy, for radiological documented SFs between January 1, 2004, and March 31, 2016. Available information was used to evaluate whether indicators of possible child abuse were documented by the ER staff and whether diagnosis of potential abuse was followed by further screening or referral to child protection agencies. During the study period, 11,136 accesses of the ER by children younger than 36 months were documented, among whom 417 presented long bone or skull fractures. Skull fractures were significantly more common among children <12 months of age (p=0.001), whereas radius/ulna and humerus fractures were diagnosed significantly more frequently in children 12-36 months of age (p=0.036 and p=0.022, respectively). Recorded medical history was considered inadequate in 255 (61.2%) cases with no difference related to patient’s age. Our study showed that the majority of charts in case of SFs were found to contain inadequate documentation to explain causes at the heart of the fractures and, therefore, to rule out any inflicted trauma. The development of specific referral guidelines, along with the continuous education and training of health professionals, as well as the preparation of structured medical forms, are essential measures to activate in order to improve the referral of children from the ER to child protection agencies.